Termination and pausing of RNA polymerase II downstream of yeast polyadenylation sites. - Hyman, L E (1993)
Little is known about the transcriptional events which occur downstream of polyadenylation sites. Although the polyadenylation site of a gene can be easily identified, it has been difficult to determine the site of transcription termination in vivo because of the rapid processing of pre-mRNAs. Using an in vitro approach, we have shown that sequences from the 3' ends of two different Saccharomyces cerevisiae genes, ADH2 and GAL7, direct transcription termination and/or polymerase pausing in yeast nuclear extracts. In the case of the ADH2 sequence, the RNA synthesized in vitro ends approximately 50 to 150 nucleotides downstream of the poly(A) site. This RNA is not polyadenylated and may represent the primary transcript. A similarly sized nonpolyadenylated [poly(A)-] transcript can be detected in vivo from the same transcriptional template. A GAL7 template also directs the in vitro synthesis of an RNA which extends a short distance past the poly(A) site. However, a significant amount of the GAL7 RNA is polyadenylated at or close to the in vivo poly(A) site. Mutations of GAL7 or ADH2 poly(A) signals prevent polyadenylation but do not affect the in vitro synthesis of the extended poly(A)- transcript. Since transcription of the mutant template continues through this region in vivo, it is likely that a strong RNA polymerase II pause site lies within the 3'-end sequences. Our data support the hypothesis that the coupling of this pause site to a functional polyadenylation signal results in transcription termination.